Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1136/svn-2021-001242
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment with or without intravenous alteplase for acute ischaemic stroke due to basilar artery occlusion

Abstract: Background and purposeIt remains controversial if endovascular treatment (EVT) can improve the outcome of patients with acute basilar artery occlusion (BAO). This study aims to compare the functional outcomes between EVT with and without intravenous thrombolysis (IVT) first in patients who had acute ischaemic stroke (AIS) due to BAO.MethodsPatients who had AIS with BAO who underwent EVT within 24 hours of onset were enrolled in this multicentre cohort study, and the efficacy and safety were compared between IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…After screening of titles and abstracts, 51 publications were reviewed in full text. A total of three studies,20–22 comparing bridging IVT with direct MT in 1096 patients with stroke due to BAO met the eligibility criteria for inclusion in our meta-analysis (figure 1). Reliability of study selection between observers was substantial at both the title and abstract screening stage (Cohen’s κ=0.83) and the full-text review stage (Cohen’s κ=1.00) 23…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After screening of titles and abstracts, 51 publications were reviewed in full text. A total of three studies,20–22 comparing bridging IVT with direct MT in 1096 patients with stroke due to BAO met the eligibility criteria for inclusion in our meta-analysis (figure 1). Reliability of study selection between observers was substantial at both the title and abstract screening stage (Cohen’s κ=0.83) and the full-text review stage (Cohen’s κ=1.00) 23…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were non-randomized multicenter retrospective cohort studies 20–22. Data were collected across large volume neurointervention centers across eight countries: China, Germany, Greece, Italy, Singapore, Sweden, Taiwan, and the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, their subgroup analysis also suggested that BAO patients with large artery atherosclerosis might benefit from bridging therapy compared with EVT alone 29. However, the findings of another study conducted by Nie et al showed that BAO patients treated with bridging therapy had better functional outcomes than those who underwent EVT alone 30…”
Section: Discussionmentioning
confidence: 99%